Laguerre Voronoi Diagram as a Model for Generating the Tessellation Patterns on the Sphere - Supanut Chaidee (2019)
© 2019, Springer Japan KK, part of Springer Nature. We propose a model for generating tessellation patterns on the sphere using the spherical Laguerre Voronoi diagram which satisfies the real-world assumptions. The generator pushing model is presented to generate the tessellation dynamically. The simulations were done for the different distribution of spherical circles on the sphere, and the results show the tendency of the distribution of resulting spherical circles.